2012
DOI: 10.1007/s00330-012-2606-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging to assess the effect of exercise training on pulmonary perfusion and blood flow in patients with pulmonary hypertension

Abstract: The study indicates that respiratory and physical exercise may improve pulmonary perfusion in patients with PH. Measurement of MR parameters of pulmonary perfusion might be an interesting new method to assess therapy effects in PH. The results of this initial study should be confirmed in a larger study group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 30 publications
3
68
0
4
Order By: Relevance
“…45,46 Furthermore, recent human studies have shown that exercise training is associated with significant improvements in central pulmonary perfusion and peripheral skeletal muscle function, which could also contribute to the training-related improvement in exercise capacity. 16,23 In this study, we observed a significant improvement in the pulmonary arterial systolic pressure with training, which could lead to significant reductions in pulmonary vascular resistance and a concomitant improvement in blood flow through the pulmonary vascular system. Improved pulmonary perfusion would be associated with improved oxygenation and cardiac output, thus leading to improvement in exercise tolerance and cardiorespiratory fitness.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…45,46 Furthermore, recent human studies have shown that exercise training is associated with significant improvements in central pulmonary perfusion and peripheral skeletal muscle function, which could also contribute to the training-related improvement in exercise capacity. 16,23 In this study, we observed a significant improvement in the pulmonary arterial systolic pressure with training, which could lead to significant reductions in pulmonary vascular resistance and a concomitant improvement in blood flow through the pulmonary vascular system. Improved pulmonary perfusion would be associated with improved oxygenation and cardiac output, thus leading to improvement in exercise tolerance and cardiorespiratory fitness.…”
mentioning
confidence: 58%
“…Several small studies have evaluated exercise training as an adjunctive therapeutic strategy in patients with chronic pulmonary hypertension. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although most of these studies were small and not designed to address clinical end points, such as mortality or hospitalizations, related to pulmonary hypertension, they have demonstrated a variable degree of improvement in exercise tolerance and quality of life in response to training.Therefore, because of the uncertainty about the benefit of structured exercise training programs in patients with pulmonary hypertension, we performed this systematic review and meta-analysis to assess the efficacy and safety of structured exercise training regimens in patients with pulmonary hypertension. …”
mentioning
confidence: 99%
“…Inicialmente, se pensaba que el incremento de la actividad física podía ser perjudicial para estos pacientes y que podía en realidad aumentar las presiones de arterias pulmonares y acerar el proceso proliferativo 21 . Actualmente, se ha observado mediante resonancia magnética un aumento significativo en la velocidad peak del flujo sanguíneo (p = 0,012) y de la perfusión pulmonar (p = 0,017) en el sujetos entrenados durante 3 semanas mientras el grupo control se mantuvo sin cambios significativos 22 . En una reciente revisión sistemá-tica y metanálisis de los artículos existentes de ejercicio en pacientes con HTP, se objetivó una reducción de la presión sistólica de arterias pulmonares en 3,7 mmHg, estadística-mente significativo 23 .…”
Section: Introductionunclassified
“…These results were confirmed by Mainguy et al (45) who demonstrated a decreased proportion of type II muscle fibers and improvement in peripheral muscle characteristics as a consequence of ET in idiopathic PAH patients. A magnetic resonance imaging (MRI) study assessed the effects of 3-weeks in-hospital exercise training on pulmonary perfusion and blood flow in patients with PAH and CTEPH showing a significant improvement of MRI parameters of pulmonary perfusion and peak flow velocity in comparison with sedentary controls (46). In the physiologic study by Kabitz et al (47), seven PAH patients received supervised (physiotherapists and © C I C E d i z i o n i I n t e r n a z i o n a l i physicians) training every for a 15-week period showing a significant improvement of respiratory muscle strength assessed by twitch mouth pressure and exercise capacity (6MWD).…”
Section: The Pathophysiological Rationale Of Exercise Training In Pahmentioning
confidence: 99%